Neural mechanisms of extinguishing drug and pleasant cue associations in human addiction: role of the VMPFC. (5th September 2017) - Konova, Anna B.; Parvaz, Muhammad A.; Bernstein, Vladimir; Zilverstand, Anna; Moeller, Scott J.; Delgado, Mauricio R.; Alia‐Klein, Nelly; Goldstein, Rita Z.
Abstract: The neurobiological mechanisms that underlie the resistance of drug cue associations to extinction in addiction remain unknown. Fear extinction critically depends on the ventromedial prefrontal cortex (VMPFC). Here, we tested if this same region plays a role in extinction of non‐fear, drug and pleasant cue associations. Eighteen chronic cocaine users and 15 matched controls completed three functional MRI scans. Participants first learned to associate an abstract cue (the conditioned stimulus, CS) with a drug‐related (CSD+ ) or pleasant (CSP+ ) image. Extinction immediately followed where each CS was repeatedly presented without the corresponding image. Participants underwent a second identical session 24 hours later to assess retention of extinction learning. Results showed that like fear extinction, non‐fear‐based extinction relies on the VMPFC. However, extinction‐related changes in the VMPFC differed by cue valence and diagnosis. In controls, VMPFC activation to the CSD+ (which was unpleasant for participants) gradually increased as in fear extinction, while it decreased to the CSP+, consistent with a more general role of the VMPFC in flexible value updating. Supporting a specific role in extinction retention, we further observed a cross‐day association between VMPFC activation and skin conductance, a classic index of conditioned responses. Finally, cocaine users showed VMPFC abnormalities for both CSs, which, in the case of the CSD+, correlated with craving. These data suggest a global deficit in extinction learning in this group that may hinder extinction‐based treatment efforts. More broadly, these data show that the VMPFC, when functionally intact, supports extinction learning in diverse contexts in humans. Abstract : In this 2‐day fMRI study we find that, like fear extinction, non-fear based extinction relies on the ventromedial prefrontal cortex (VMPFC). However, we additionally find that extinction‐related changes in the VMPFC differ by (1) what is being extinguished (drug‐related versus pleasant cues) and (2) drug addiction diagnosis. While healthy individuals show progressive, cue‐specific changes in VMPFC activation, chronic cocaine users do not, suggesting a global extinction‐learning deficit in this group that may hinder extinction‐based treatment efforts. .